MENGAJARKAN ANAK UNTUK TETAP WASPADA DENGAN MEMATUHI PROKES AGAR TERHINDAR DARI BAHAYA COVID 19 DISEKOLAH TKIT DAARUNAHL TAHUN 2022 - Heny Sasmita; Ucu Wandi Somantri; Dian Nastiti; Eneng Dety Nurbaeti; Ruben Fuad Baktiar; Siti Mutimainah (Universitas Gajah Putih, Indonesia, 2022)
The coronavirus pandemic in indonesia affects all age groups, including children. The incidence of covid-19 in children reaches 5% of the total incidence. The clinical manifestations of covid-19 in children often resemble seasonal diseases such as fever, cough, flu, and diarrhea, so parents ignore the child's condition without realizing that these symptoms are the smallest threat to the spread of covid-19 in the social sphere because children are the age at which a group of people are vulnerable to exposure to covid-19. Parents must be able to prepare their children to minimize exposure to the covid-19 virus by maximizing the implementation of health protocols in daily life. This community service was carried out by 3 lecturers from the faculty of science, pharmacy and health unma banten with the help of several students. This activity was guided and practiced at tkit daaru nahl cilegon which numbered 25 people so that children were not exposed to covid-19 as well as knowing correctly how to wash hands properly and correctly, complying with the covid-19 health protocols, and knowing how important it is to wear a mask during the covid-19 pandemic. With this community service, it is hoped that the application of hand washing with running water, not only using hand sanitizers, especially when hands look dirty and oily, but is done using running water and soap.